Effects of Sedation with Medetomidine and Dexmedetomidine on Doppler Measurements of Ovarian Artery Blood Flow in Bitches - Paloma Nicolás-Barceló; Martina Facchin; Fernando Martínez-Taboada; Rafael Barrera; José Ignacio Cristóbal; Mario Alberto González; Ángela Durán-Galea; Beatriz Macías-García; Francisco Javier Duque (Animals, 2021)
The aim was to evaluate if medetomidine and dexmedetomidine affected arterial ovarian blood flow in dogs. The dogs were randomly assigned to two different groups. In Group 1, medetomidine (10 µg/kg) was administered intramuscularly and, in Group 2, dexmedetomidine (5 µg/kg) was used. After a preliminary exam, arterial blood pressure (BP) was measured and a duplex Doppler ultrasonographic examination of both ovarian arteries was performed. Twenty minutes after the administration of medetomidine or dexmedetomidine, BP and ovarian Doppler ultrasonography were repeated. High quality tracings of ovarian artery flow velocity were obtained in all dogs and Doppler parameters: Peak Systolic Velocity (PSV), End Diastolic Velocity (EDV) and Resistive Index (RI) were measured before and after drug administration in the left (LO) and right (RO) ovaries. PSV and EDV values decreased significantly after drug administration (p < 0.05) compared to the non-sedated values, but no differences were found between the LO and RO (p > 0.05). The RI was not affected by drugs administration in neither of the groups studied (p > 0.05). In conclusion, the administration of medetomidine or dexmedetomidine causes a decrease in blood flow velocity in the ovarian artery and may be a good choice to avoid excessive bleeding prior surgeries in which ovariectomy.